2011
DOI: 10.1038/ng.971
|View full text |Cite
|
Sign up to set email alerts
|

A primary microcephaly protein complex forms a ring around parental centrioles

Abstract: Autosomal recessive primary microcephaly (MCPH) is characterised by a significant reduction in prenatal human brain growth, without alteration of cerebral architecture. The genetic aetiology of MCPH is bi-allelic mutations in genes coding for a subset of centrosomal proteins1-10. While at least three of these proteins have been implicated in centrosome duplication11, the nature of centrosome dysfunction that underlies the neurodevelopmental defect in MCPH is unclear. Here we report a homozygous MCPH-causing mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
217
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(243 citation statements)
references
References 53 publications
24
217
1
1
Order By: Relevance
“…In these systems centrosome inactivation was consistently linked to impaired centrosomal MT-nucleation and the loss of centrosomal PCM components including c-tubulin and Cep63. In this current study, however, we failed to detect a loss of PCM components required for mitotic centrosome function and centrosomal spindle assembly in human cancer cells (Doxsey et al, 1994;Fong et al, 2008;Gomez-Ferreria et al, 2007;Graser et al, 2007;Haren et al, 2009;Sir et al, 2011;Smith et al, 2009;Zhu et al, 2008;Zimmerman et al, 2004). Instead, we consistently detected c-tubulin, Cep63, Pericentrin, Cep192 (the human ortholog of Drosophila SPD2) and Cep215 (the human ortholog of Drosophila centrosomin) at free mitotic centrosomes (Fig.…”
Section: Transient Detachment Of Individual Centrosomes From the Assementioning
confidence: 56%
“…In these systems centrosome inactivation was consistently linked to impaired centrosomal MT-nucleation and the loss of centrosomal PCM components including c-tubulin and Cep63. In this current study, however, we failed to detect a loss of PCM components required for mitotic centrosome function and centrosomal spindle assembly in human cancer cells (Doxsey et al, 1994;Fong et al, 2008;Gomez-Ferreria et al, 2007;Graser et al, 2007;Haren et al, 2009;Sir et al, 2011;Smith et al, 2009;Zhu et al, 2008;Zimmerman et al, 2004). Instead, we consistently detected c-tubulin, Cep63, Pericentrin, Cep192 (the human ortholog of Drosophila SPD2) and Cep215 (the human ortholog of Drosophila centrosomin) at free mitotic centrosomes (Fig.…”
Section: Transient Detachment Of Individual Centrosomes From the Assementioning
confidence: 56%
“…The depletion of PCM proteins cdk5rap2 or pericentrin, with the latter also genetically linked to primordial dwarfism with associated microcephaly, similarly altered neuroprogenitor division in embryonic mouse brains with reduced cell proliferation and enhanced cell cycle exit (Buchman et al, 2010;Lizarraga et al 2010). However, unlike MCPH proteins (cdk5rap2, CENPJ, STIL, Cep152, Cep135 and Cep63) with well characterized functions in centriole duplication (Barrera et al 2010;Delattre et al, 2004;Hatch et al, 2010;Hussain et al, 2012;Sir et al, 2011;Vulprecht et al, 2012), we have demonstrated that WDR62 is not principally a centrosome protein and its depletion did not obviously impact on centrosome number or structure during interphase. We cannot completely exclude WDR62 functions as an integral centrosomal protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that centrosomal PD proteins prevent centriole overduplication, for instance by promoting engagement between the mother centriole and its procentriole [38,103,104]. Recent studies suggest that ORC1 exercises centrosome copy number control by suppressing CDK2-cyclin E-dependent reduplication of centrioles, a function specifically disrupted by Meier-Gorlin mutations in ORC1 [91].…”
Section: Centrosomes and Body Size (A) Primordial Dwarfism Syndromesmentioning
confidence: 99%